Risk factors for developing cardiovascular disease in women - Raíssa Santos Vieira; Adriana Martins Gallo; Cesar Junior Aparecido de Carvalho; Juliane Pagliari Araujo; Rosangela Cabral; Gabrielle Jacklin Eler (Universidad de Antioquia, 2017)
Objective. To evaluate the factors that predispose to the development of cardiovascular diseases in women who were attended at a Basic Health Unit in Londrina, Paraná, Brazil. Methods. The research was characterized as observational and quantitative. The population sample consisted of 60 women aged over 18 years, being chosen at random. For data collection, mHealth Data Collector (mHDC), a mobile device, was used with a questionnaire on daily habits, health status, and disease. Measurements were made of glucose and blood cholesterol, blood pressure and anthropometric measurements. Data collection took place in February 2014 to November 2014. Results. Risk factors were overweight / obesity (63.8%) and sedentary lifestyle (65%), followed by family history of cardiovascular disease (43.3%), hypercholesterolemia (38.3%), and hypertension (13.3%). Conclusion. This population of women presented risk factors for the development of cardiovascular disease in all ages, being necessary the implementation of measures that stimulate changes in the daily habits and improve health conditions among women by the health team.   How to cite this article: Vieira RS, Gallo AM, Carvalho CJA, Araujo JP, Cabral R, Eler GJ. Risk factors for developing cardiovascular disease in women. Invest. Educ. Enferm. 2016; 35(1):